2019
DOI: 10.1155/2019/3201458
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activity Screening of Ethanol Extract of Lavandula stoechas and Investigation of Its Biochemical Composition

Abstract: The aim of this study was to test antimicrobial activity of ethanol extract of Lavandula stoechas against 22 bacteria and 1 yeast. Also, biochemical composition of the extract was investigated. A wide range of Gram-positive, Gram-negative microorganisms, and multidrug resistant bacteria were selected to test the antimicrobial activity. As a result, the extract is observed to contain fenchone (bicyclo[2.2.1]heptan-2-one, 1,3,3-trimethyl-, (1R)-) and camphor (+)-2-bornanone) as major components and showed antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“… The values are presented in MIC or MIC/MLC (µg/mL or µL/mL *). LP [ 8 , 38 , 43 , 44 , 128 , 138 ]; LS [ 46 , 51 , 56 , 57 , 58 , 60 , 62 , 63 , 65 , 86 , 139 , 140 , 141 , 142 ]; LSL [ 7 , 15 , 19 , 20 , 21 , 36 , 63 , 75 , 76 , 128 , 138 ]; LSS [ 40 , 77 , 80 , 82 ]; LV [ 85 ]. EO: essential oil; NPE: non-polar extract; PE: polar extract.…”
Section: Figurementioning
confidence: 99%
“… The values are presented in MIC or MIC/MLC (µg/mL or µL/mL *). LP [ 8 , 38 , 43 , 44 , 128 , 138 ]; LS [ 46 , 51 , 56 , 57 , 58 , 60 , 62 , 63 , 65 , 86 , 139 , 140 , 141 , 142 ]; LSL [ 7 , 15 , 19 , 20 , 21 , 36 , 63 , 75 , 76 , 128 , 138 ]; LSS [ 40 , 77 , 80 , 82 ]; LV [ 85 ]. EO: essential oil; NPE: non-polar extract; PE: polar extract.…”
Section: Figurementioning
confidence: 99%
“…Several studies have reported that the aqueous and alcoholic extracts of L. stoechas are characterized by various biological effects. Indeed, [12,13], antifungal [14], antioxidant [14,15], antihyperglycemic activities [16], anticonvulsant, antispasmodic, and sedative effects [17], and anti-inflammatory activity [17][18][19] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Man et al [18] demonstrated that Lavandula angustifolia extract had antibacterial activity. Canli et al [19] evaluated the antimicrobial activity of Lavandula stoechas ethanol extract against 22 bacteria and 1 yeast, and the results confrmed the lavender's antimicrobial activity. Recently, Sharifzadeh et al [20] reported that Lavandula coronopifolia Poir, whose extract was studied in the present work, has considerable antioxidant and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%